Relationships between ice water content and volume extinction coefficient from in situ observations for temperatures from 0° to -86°C: Implications for spaceborne lidar retrievals - Heymsfield, Andrew (author); Winker, Dave (author); Avery, Melody (author); Vaughan, Mark (author); Diskin, Glenn (author); Deng, Min (author); Mitev, Valentin (author); Matthey, Renaud (author) (Journal of Applied Meteorology and Climatology, 2014)
An examination of 2 yr of Cloud–Aerosol Lidar Infrared Pathfinder Satellite Observations (CALIPSO) lidar observations and CloudSat cloud radar observations shows that ice clouds at temperatures below about -45°C frequently fall below the CloudSat radar’s detection threshold yet are readily detectable by the lidar. The CALIPSO ice water content (IWC) detection threshold is about 0.1 versus 5 mg m⁻³ for CloudSat. This comparison emphasizes the need for developing a lidar-only IWC retrieval method that is reliable for high-altitude ice clouds at these temperatures in this climatically important zone of the upper troposphere. Microphysical measurements from 10 aircraft field programs, spanning latitudes from the Arctic to the tropics and temperatures from −86° to 0°C, are used to develop relationships between the IWC and volume extinction coefficient σ in visible wavelengths. Relationships used to derive a radiatively important ice cloud property, the ice effective diameter De, from σ are also developed. Particle size distributions (PSDs) and direct IWC measurements, together with evaluations of the ice particle shapes and comparisons with semidirect extinction measurements, are used in this analysis. Temperature-dependent De(σ) and IWC–σ relationships developed empirically facilitate the retrieval of IWC from lidar-derived σ and De values and for comparison with other IWC observations. This suite of empirically derived relationships can be expressed analytically. These relationships can be used to derive IWC and De from σ and are developed for use in climate models to derive σ from prognosed values of IWC and specified PSD properties.